Vascular endothelial growth factor receptor-3 is independently associated with cervical lymph node metastasis in papillary thyroid carcinoma - Chao, Ting-Ting; Maa, Hung-Chune; Hsia, Te-Lin; Pei, Dee; Liang, Yao-Jen; Chou, Shuo-Jiun; Chen, Yen-Lin (European Journal of Oncology and Environmental Health, 2015)
Objective: Papillary thyroid carcinoma (PTC) is the most common type of thyroid cancer. Despite excellent prognosis, the presence of cervical lymph node metastasis (cLNM) has a significant impact on tumor recurrence. However, the clinical management of cLNM remains controversial. The present study aims to shed light on the correlation between markers for hypoxia, angiogenesis and lymphangiogenesis, as well as cLNM in PTC. Methods: Ninety-five paraffin-embedded surgical specimens of PTC were constructed into tissue microarray. Immunohistochemical staining for markers of hypoxia (HIF-1α and CA-IX), angiogenesis (VEGF-A, VEGF-C and VEGFR-2), and lymphangiogenesis (VEGF-C, VEGF-D and VEGFR-3) was performed. A Kaplan-Meier plot of recurrence was performed according to the VEGFR-3 status. Results: Out of all the PTC cases, 11.6% had cLNM. CA-IX, VEGF-D and VEGFR-2 were associated with capsule invasion. Of the biomarkers, VEGF-C and VEGFR-3 were correlated with cLNM. The Kappa coefficient test showed that HIF-1α and CA-IX correlated with VEGF-A, which, together with VEGF-C, correlated with both VEGFR-2 and VEGFR-3. In contrast, VEGF-D was only associated with VEGF-C. Conclusions: VEGF-C and VEGFR-3 are associated with cLNM but only VEGFR-3 independently correlates with cLNM after adjustments for TMN staging. It may be useful to perform VEGFR-3 immunostaining in primary resected thyroid carcinoma specimens.